Conserved and Divergent Principles of Planar Polarity Revealed by Hair Cell Development and Function - Deans, Michael R. (Frontiers in Neuroscience, 2021)
Planar polarity describes the organization and orientation of polarized cells or cellular structures within the plane of an epithelium. The sensory receptor hair cells of the vertebrate inner ear have been recognized as a preeminent vertebrate model system for studying planar polarity and its development. This is principally because planar polarity in the inner ear is structurally and molecularly transparent and therefore easy to visualize. Inner ear planar polarity is also functionally significant because hair cells are mechanosensors stimulated by sound or motion and planar polarity underlies the mechanosensory mechanism, thereby facilitating the auditory and vestibular functions of the ear. Structurally, hair cell planar polarity is evident in the organization of a polarized bundle of actin-based protrusions from the apical surface called stereocilia that is necessary for mechanosensation and when stereociliary bundle is disrupted auditory and vestibular behavioral deficits emerge. Hair cells are distributed between six sensory epithelia within the inner ear that have evolved unique patterns of planar polarity that facilitate auditory or vestibular function. Thus, specialized adaptations of planar polarity have occurred that distinguish auditory and vestibular hair cells and will be described throughout this review. There are also three levels of planar polarity organization that can be visualized within the vertebrate inner ear. These are the intrinsic polarity of individual hair cells, the planar cell polarity or coordinated orientation of cells within the epithelia, and planar bipolarity; an organization unique to a subset of vestibular hair cells in which the stereociliary bundles are oriented in opposite directions but remain aligned along a common polarity axis. The inner ear with its complement of auditory and vestibular sensory epithelia allows these levels, and the inter-relationships between them, to be studied using a single model organism. The purpose of this review is to introduce the functional significance of planar polarity with regards to auditory and vestibular hair cell function and our contemporary understanding of the developmental mechanisms associated with organizing planar polarity at these three cellular levels.